Vertebrate predation on Holm Oak, Quercus ilex, acorns in a fragmented habitat: effects on seedling recruitment - Santos, T.; Tellería, J. L. (Forest Ecology and Management, 1997)
Rodent and avian consumption of Holm Oak, Quercus ilex, acorns were examined in central Spain during two high-production seasons, 1990-1991 and 1993-1994, in 1 and 3 large stands and in 6 and 10 small stands (0.2-12 ha) respectively, to study the effects of vertebrate predation on seedling recruitment. Previous data indicate that wood mouse abundance is much higher in small stands. Tree size, frequency of acorn-bearing oaks and acorn abundance were similar in the two sizes of forest stands. Overall acorn consumption was 33.7 times higher in the small stands compared to that in the large stands in 1991, and 3.1 times larger in 1994. Consumption of acorns by mice in the small stands was 49 and 95 times greater than that by birds in the first and second year, respectively. Seedling recruitment was significantly higher in the large stands in both study seasons. Regeneration by ramets was roughly similar in small and large stands in both seasons. Thus, predation by mice was apparently responsible for the failure of sexual reproduction in the small stands. The results suggest that vegetative regeneration might be the prevalent reproductive method of Holm Oaks in small forest tracts.
Keywords: acorns; Forest fragmentation; oak; Seedling; Vertebrate predation